Strategies for Pan-European Implementation of Blended Learning for Innovation and Entrepreneurship (I&E) Education - Galena Pisoni (MDPI AG, 2019)
New information and communication technologies (ICTs) provide educators and learners with novel approaches to enhance teaching and learning processes. Technology enabled learning plays a vital role in contemporary education and blended learning is widely adopted across higher education as a learning mode. In this paper we reflect on the strategies for introducing blended learning in a network of European universities and the first lessons learnt from the experience. A total of 18 universities took part with around 350 students registered in the 2018−2019 academic year. In this report we recount how the lecturers in our network introduced the blended learning in their classes, the different types of lessons resulting from this effort, as well as the teachers’ and students’ perceptions regarding the blended learning activities performed. Our reflection is focused on the use of blended learning and its positive effect on activating students and development of innovation and entrepreneurship soft skills. The perceptions on blended learning are interrelated, with the success of the blending models depending on the blended learning activities, and how well the respective online contents are embedded into the teaching and learning processes.